Upaya Meningkatkan Keterampilan Berpikir Kritis Siswa Melalui Model Pembelajaran Student Facilitator and Explaining Pada Tema Daerah Tempat Tinggalku di SD - Risnawaty Nadeak; Dewi Anzelina; Bogor Lumbanraja; Regina Sipayung; Darinda Sofia Tanjung; Reflina Sinaga; Rumiris Lumban Gaol (Departement of Mathematics Education, 2023)
This study aims to improve students' critical thinking skills through the student facilitator and explaining learning model on the theme of the area where I live in elementary school. Based on the data obtained from the average results in the pre test, post test cycle I, and cycle II, there can be an increase. The improvement process can be seen through the pre-test results there were 5 students who were complete and 20 students who were not complete with an average score of 54.72, in cycle I there were 11 students who were complete and 14 students who were not complete with an average score of 66.72, and in cycle II there were 21 students who were complete and 4 students who were not complete with an average score of 80.24.From the data obtained, it can be seen that there was an increase in the results of students' critical thinking skills classically. In the pre-test, the classical result was 20%, in cycle I it was 44%, and in cycle II it was 84%. This shows that the expected completeness of students' critical thinking results classically, which is 75%, has been achieved. Based on the increase obtained from the student learning outcomes data that the pre test to post test cycle I experienced an increase of 12, and from post test cycle I to cycle II experienced an increase of 13.52. This proves that using the Student Facilitator and Explaining learning model can improve students' critical thinking skills.